Adipokine levels and T786C polymorphism of eNOS gene promoter correlation in patients with arterial hypertension - Pidruchna Svitlana; Zakharchuk Uliana; Svan Olga; Zablotskyi Bohdan; Tokarskyy Oleksandr (Endocrine Regulations)
Objective. Genetic factors contribute to the development of metabolic syndrome and subsequent arterial hypertension (AH). The study of the T786C polymorphism of the endothelial nitric oxide synthase (eNOS) gene in arterial hypertension is important as its correlation with adipokine imbalance is a novelty area to find associations between hypertension development, obesity, and heredity. The purpose of the current study was to investigate serum adipokines levels, depending on the T786C polymorphism of the eNOS in patients with arterial hypertension.